Phonological Awareness of English among Saudi Learners: An Examination of the Role of Lexical Status and Intra-syllabic Phonological Unit - Alasmari, Amal (International Journal of Language and Literary Studies, 2024)
This study explores phonological awareness ability in the second language. Although some studies have examined L2 phonological awareness, most of these studies have not provided sufficient details on the type of stimulus items employed in these studies nor considered the possible effect of some linguistic factors on the results. Thus, the study aims to explore the impact of the lexical status of the item on phonological awareness in L2. In addition, the study examines the preferred intra-syllabic phonological unit in L2 among Saudi university students. Specifically, the study examines the effect of the lexical status (word vs non-word) and the intra-syllabic phonological unit (onset-rime vs. body-coda) on the phonological awareness of English. The participants were 48 university students majoring in English language. Two phonological awareness tasks were administered to test phonological awareness at the intra-syllabic and phonotactic levels. The tasks were an intra-syllabic segmentation task and a lexical decision task. The results showed significant effects of both linguistic factors on the participants’ L2 phonological awareness. The lexical status of the test item had a significant effect on the participants’ performance in the task. The participants performed significantly better in identifying real-words than non-words, which reflects an advanced phonotactic awareness. Finally, the results revealed that the body-coda unit is the preferred intra-syllabic structure for Saudi learners. Therefore, the study provides evidence that the onset-rime hypothesis is not universal and is at least not applicable to Saudi Arabic speakers. The study offers theoretical and practical implications for the acquisition and teaching of L2.